Metodología de investigación en estudios de usuarios - Martín Moreno, Carmen (Revista General de Información y Documentación, 2008)
The brief review of the history of user studies set out in this paper serves as an introduction to their definition and important role in information centres, as well as to the methods available for gathering information on users. The resulting overview of the literature is followed by a discussion of the methods used to date, where general considerations give way to an analysis of the particulars, based on an initial classification of users as active or passive information providers. The main techniques along with their advantages and drawbacks, the type of information that can be obtained with each technique and the utility of such information for the various information centre departments are also described. The final section discusses scientific methodology in general, and naturally the need to use scientific method in any type of research, in this case user surveys. The advantages afforded by the implementation of such methodology in these studies are also examined.